2014
DOI: 10.1017/s0031182014000018
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating parasite data in population structure studies of South African sardine Sardinops sagax

Abstract: A multidisciplinary approach has been applied to examine the population structure of sardine Sardinops sagax off South Africa, where this species supports significant fisheries and is also of ecological and eco-tourism importance. Observations of discontinuous sardine distribution patterns, discrete spawning grounds and significant spatial differences in a variety of phenotypic characteristics have suggested the existence of discrete western, southern and eastern sardine sub-populations or stocks. The use of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…By increasing the knowledge we have on parasite loads and infection patterns, and expanding the sampled species and areas, we can make more informed management decisions regarding commercially important fish species. For example; Reed et al (2012), MacKenzie and Abaunza 2005 and van der Lingen et al (2015) documented the parasite assemblage of South African sardine Sardinops sagax and identified a digenean parasite biotag which subsequent studies have shown to provide strong evidence for multiple sardine stocks (van der Lingen et al, 2015; Weston et al, 2015). Stock-specific sardine assessment models that incorporate these parasite data have been developed (De Moor et al, 2017) and are now used in management of the sardine fishery.…”
Section: Discussionmentioning
confidence: 99%
“…By increasing the knowledge we have on parasite loads and infection patterns, and expanding the sampled species and areas, we can make more informed management decisions regarding commercially important fish species. For example; Reed et al (2012), MacKenzie and Abaunza 2005 and van der Lingen et al (2015) documented the parasite assemblage of South African sardine Sardinops sagax and identified a digenean parasite biotag which subsequent studies have shown to provide strong evidence for multiple sardine stocks (van der Lingen et al, 2015; Weston et al, 2015). Stock-specific sardine assessment models that incorporate these parasite data have been developed (De Moor et al, 2017) and are now used in management of the sardine fishery.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, studies on sardines (food source of penguins) did record higher densities of sardines and specifically higher densities of Cardiocephaloides spp. infected sardines along the south-western coast between Cape Point and Cape Agulhas (Mhlongo et al ., 2013; Van der lingen et al ., 2015). From this evidence, it is possible that the presence of intermediate and definitive hosts facilitates a higher incidence of Cardiocephaloides spp.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of co-occurring congeneric and confamilial bird can further increase host and nest density, which can result in higher abundances and transmission of bird-specific parasites (Duffy, 1988). The level of parasite infestation in prey species can also vary spatially and may influence the risk of infection for seabirds that act as definitive hosts (Van der lingen et al, 2015;Levsen et al, 2018). A large scale study by Levsen et al (2018) recorded regional difference in parasite infestations of Anisakid nematodes in sardine (Sardina pilchardus) and other commercial fish species within the European fishing grounds.…”
Section: Introductionmentioning
confidence: 99%
“…Three putative ecologically or functionally discrete stocks or subpopulations of S. sagax occur off the coast of South Africa, namely western, southern and eastern subpopulations (van der Lingen 2011;van der Lingen et al 2015). For the purposes of this study, sardine were collected from all three subpopulations and, in accordance with Whittington et al (2008), it was assumed that if the virus was present it would be found in at least 10% of adult fish, would be uniformly distributed among shoals of fish within a subpopulation and among schools within shoals, and fish sampled for PHV testing would be representative of the subpopulation from which they were caught.…”
Section: Determination Of Phv Presence In South African Sardinementioning
confidence: 99%